Diagnosis and treatment of flow limitation with a controllable airway resistance - a software simulation. Issue 5 (2016) - Laufer, Bernhard; Krüger-Ziolek, Sabine; Schullcke, Benjamin; Kretschmer, Jörn; Möller, Knut
Abstract: An easy and available manoeuvre to treat flow limitation in severe COPD (chronic obstructive pulmonary disease) is pursed lip breathing. However, in unconscious or sleeping patients or patients who can't overcome the painful and panic triggering effects of dyspnoea through blocked airways, a device to treat flow limitation would be very helpful. Based on a first order lung model enhanced by flow limitation, a simulation to analyze the influence of a controllable airway resistance on flow limitation is presented and evaluated. The effects of flow limitation can be reduced considerably.